Altering the balance between AOX1A and NDB2 expression affects a common set of transcripts in Arabidopsis - Sweetman, Crystal; Waterman, Christopher D.; Wong, Darren C.J.; Day, David A.; Jenkins, Colin L.D.; Soole, Kathleen L. (Frontiers in Plant Science, 2022)
Stress-responsive components of the mitochondrial alternative electron transport pathway have the capacity to improve tolerance of plants to abiotic stress, particularly the alternative oxidase AOX1A but also external NAD(P)H dehydrogenases such as NDB2, in Arabidopsis. NDB2 and AOX1A can cooperate to entirely circumvent the classical electron transport chain in Arabidopsis mitochondria. Overexpression of AOX1A or NDB2 alone can have slightly negative impacts on plant growth under optimal conditions, while simultaneous overexpression of NDB2 and AOX1A can reverse these phenotypic effects. We have taken a global transcriptomic approach to better understand the molecular shifts that occur due to overexpression of AOX1A alone and with concomitant overexpression of NDB2. Of the transcripts that were significantly up- or down- regulated in the AOX1A overexpression line compared to wild type (410 and 408, respectively), the majority (372 and 337, respectively) reverted to wild type levels in the dual overexpression line. Several mechanisms for the AOX1A overexpression phenotype are proposed based on the functional classification of these 709 genes, which can be used to guide future experiments. Only 28 genes were uniquely up- or down-regulated when NDB2 was overexpressed in the AOX1A overexpression line. On the other hand, many unique genes were deregulated in the NDB2 knockout line. Furthermore, several changes in transcript abundance seen in the NDB2 knockout line were consistent with changes in the AOX1A overexpression line. The results suggest that an imbalance in AOX1A:NDB2 protein levels caused by under- or over-expression of either component, triggers a common set of transcriptional responses that may be important in mitochondrial redox regulation. The most significant changes were transcripts associated with photosynthesis, secondary metabolism and oxidative stress responses.